Cardiovascular effect of Nigella sativa L. Aqueous Extract in Normal Rats - Hebi, Morad; Zeggwagh, Naoufel; Hajj, Lhoussaine; El Bouhali, Bachir; Eddouks, Mohamed (Cardiovascular & Haematological Disorders - Drug Targets, 2016)
This study aims to evaluate the cardiovascular effect of Nigella sativa L. aqueous extract (NSAE) in normal rats. The in vivo experiment showed that the intravenous injection of NSAE at the doses of 50, 100 and 200 mg/kg of body weight produced a dose dependent reduction in the mean arterial blood pressure (MABP) (p<0.001) accompanied by a significant fall in heart rate (p<0.01). In the in vitro experiment, incubation of NSAE during 30 min caused a right shift of the contraction response curve of aortic ring to Norepinephrine (NE) with a reduction of the maximal contraction response (p<0.01). Endothelium destruction significantly reduced the vasorelaxant effect of NSAE at a dose of 30 mg/ml (p<0.01). Furthermore, Nitric oxide synthase inhibitor: Nω-Nitro-L-Arginine Methyl Ester (L-NAME) produced a significant reduction (p<0.01) of the in vitro vasorelaxant effect of NSAE at a dose of 30 mg/ml. We conclude that NSAE possess a rapid and dose dependent in vivo hypotensive effect in normal rats which may be probably due to the inhibition of parasympathetic tone. In isolated aortic ring, NSAE possess a potent inhibitor of contractile response to NE which may be probably due to an increase in the endothelial nitric oxide synthesis.
Keywords: Aqueous extract